American music - Candelaria, Lorenzo (Thomson/Schirmer, 2007)
This best-selling survey text describes American music as a panorama of distinct yet parallel streams-popular, folk, sacred, and classical-that reflect the uniquely diverse character of the United States. Comparing and contrasting musical styles across regions and time, Candelaria and Kingman deliver a vision of American music both exuberant and inventive, a music that arises out of the history and musical traditions of the many immigrants to America's shores